2022
DOI: 10.1038/s41598-022-13052-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hub pathways and drug candidates in gastric cancer through systems biology

Abstract: Gastric cancer is the fourth cause of cancer death globally, and gastric adenocarcinoma is its most common type. Efforts for the treatment of gastric cancer have increased its median survival rate by only seven months. Due to the relatively low response of gastric cancer to surgery and adjuvant therapy, as well as the complex role of risk factors in its incidences, such as protein-pomp inhibitors (PPIs) and viral and bacterial infections, we aimed to study the pathological pathways involved in gastric cancer d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…The turquoise module was the largest module comprising 139 genes and also identified pathways that were related to other cancers such as breast cancer, gastric cancer, and retinoblastoma. Gastric adenocarcinoma has been reported to be correlated to the investigated cancers including liver carcinoma and lung cancer through specific genes [ 42 ]. It was noted that some genes were shared between the detected cancer pathways, this included the AURKA gene, which was involved in the gastric and breast cancer pathways.…”
Section: Resultsmentioning
confidence: 99%
“…The turquoise module was the largest module comprising 139 genes and also identified pathways that were related to other cancers such as breast cancer, gastric cancer, and retinoblastoma. Gastric adenocarcinoma has been reported to be correlated to the investigated cancers including liver carcinoma and lung cancer through specific genes [ 42 ]. It was noted that some genes were shared between the detected cancer pathways, this included the AURKA gene, which was involved in the gastric and breast cancer pathways.…”
Section: Resultsmentioning
confidence: 99%
“…In their study, overexpression of signaling pathways, including extracellular matrix organization, cell division, and cell cycle, as well as downregulation of ion transport and digestion pathways were also indicated. They also reported that their identified hub genes in gastric adenocarcinoma participated in platelet activation, focal adhesion, gastric acid secretion, cell cycle and HPV infection pathways [ 66 ]. In 2018, Saberi Anvar et al used a systems biology approach for GC biomarkers and found that cell cycle, neutropin signaling pathway and nucleotide excision are the most enriched signals.…”
Section: Discussionmentioning
confidence: 99%
“…45 FBN1 gene involvement in the pathways of platelet activation was discovered in a recent work focused on a multilayer systems biology investigation of gastric cancer. 46 Besides, activated fibrinolysis, thrombin and platelet dysfunction are less well known but are indeed important features of Marfan syndrome. 47 The above information may provide us preliminary insight into exploring the effect of FBN2 gene on bleeding of drugs.…”
Section: Discussionmentioning
confidence: 99%
“…It might mediate cell adhesion by interacting with the cell surface receptors integrins ITGAV:ITGB3 and ITGA5:ITGB1, 43,44 and subsequently bind heparin, resulting in assembly of microfibrils 45 . FBN1 gene involvement in the pathways of platelet activation was discovered in a recent work focused on a multilayer systems biology investigation of gastric cancer 46 . Besides, activated fibrinolysis, thrombin and platelet dysfunction are less well known but are indeed important features of Marfan syndrome 47 .…”
Section: Discussionmentioning
confidence: 99%